2015
DOI: 10.1038/srep17257
|View full text |Cite
|
Sign up to set email alerts
|

A chimeolysin with extended-spectrum streptococcal host range found by an induced lysis-based rapid screening method

Abstract: The increasing emergence of multi-drug resistant streptococci poses a serious threat to public health worldwide. Bacteriophage lysins are promising alternatives to antibiotics; however, their narrow lytic spectrum restricted to closely related species is a central shortcoming to their translational development. Here, we describe an efficient method for rapid screening of engineered chimeric lysins and report a unique “chimeolysin”, ClyR, with robust activity and an extended-spectrum streptococcal host range ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 58 publications
4
70
0
Order By: Relevance
“…Although, Endolysins completely act proprietary for each species, some endolysins have a wide host range, as shown in a study by Yang et al in 2015. They showed a unique "chimeolysin", ClyR, with robust activity, and an extended-spectrum streptococcal host range, most streptococcal species, as well as representative enterococcal and staphylococcal species (50). Similar studies have been reported that LysK, from staphylococcal phage K, has been activated against 9 Staphylococcus species from both human and bovine sources, including MRSA.…”
Section: Sepsissupporting
confidence: 58%
“…Although, Endolysins completely act proprietary for each species, some endolysins have a wide host range, as shown in a study by Yang et al in 2015. They showed a unique "chimeolysin", ClyR, with robust activity, and an extended-spectrum streptococcal host range, most streptococcal species, as well as representative enterococcal and staphylococcal species (50). Similar studies have been reported that LysK, from staphylococcal phage K, has been activated against 9 Staphylococcus species from both human and bovine sources, including MRSA.…”
Section: Sepsissupporting
confidence: 58%
“…However, no studies to date have reported on lysins effective against S. mutans biofilms. ClyR is a chimeolysin engineered from two parental streptococcal lysins and is the first lysin reported to be active against planktonic S. mutans cells (22). In the present study, we report the efficacy of ClyR in preventing and removing biofilms formed by S. mutans under both physiological and cariogenic conditions.…”
mentioning
confidence: 77%
“…The swabs were placed in 400 l PBS, sonicated for 1 min, and plated on mitis salivarius-bacitracin agar plates containing 15% sucrose, 0.2 g/ml bacitracin, 0.001% potassium tellurate for enumeration of the plaque CFU. After the 3-week treatment, the serum and saliva were monitored for the presence of ClyR-specific antibodies for another 2 weeks by enzyme-linked immunosorbent assay (ELISA), as described previously (22). The body weight of each mouse was also measured weekly.…”
Section: Bacterial Strains Bacterial Strains (Seementioning
confidence: 99%
“…Native CD and CWBD were joined via a linker to develop chimeolysins (e.g. Lys168-87, Lys170-87, B30-182-lyso, Ply187N-V12C and ClyR), which showed broad antibacterial spectrum [112,115]. One such chimeolysin, ClyR, effectively lyses Streptococcal spp.…”
Section: Endolysins-phage Enzymes Degrading Peptidoglycanmentioning
confidence: 99%
“…(S. pyogenes, S. agalactiae, S. dysgalactiae, S. equi, S. mutans, S. pneumoniae, S. suis and S. uberis), E. faecalis and S. aureus, including MRSA [115]. The chimeolysin ClyR is also effective in killing Streptococcus mutans, which colonizes as biofilm on tooth surface [115].…”
Section: Endolysins-phage Enzymes Degrading Peptidoglycanmentioning
confidence: 99%